The white dwarf binary pathways survey – VI. Two close post-common envelope binaries with TESS light curves. Issue 2 (7th March 2022) - Hernandez, M S; Schreiber, M R; Parsons, S G; Gänsicke, B T; Toloza, O; Tovmassian, G; Zorotovic, M; Lagos, F; Raddi, R; Rebassa-Mansergas, A; Ren, J J; Tappert, C
Abstract: Establishing a large sample of post-common-envelope binaries (PCEBs) that consist of a white dwarf plus an intermediate mass companion star of spectral type AFGK, offers the potential to provide new constraints on theoretical models of white dwarf binary formation and evolution. Here, we present a detailed analysis of two new systems, TYC 110-755-1 and TYC 3858-1215-1. Based on radial velocity measurements, we find the orbital periods of the two systems to be ∼0.85 and ∼1.64 d, respectively. In addition, HST spectroscopy of TYC 110-755-1 allowed us to measure the mass of the white dwarf in this system (0.78 M⊙ ). We furthermore analysed TESS high-time-resolution photometry and find both secondary stars to be magnetically extremely active. Differences in the photometric and spectroscopic periods of TYC 110-755-1 indicate that the secondary in this system is differentially rotating. Finally, studying the past and future evolution of both systems, we conclude that the common envelope efficiency is likely similar in close white dwarf plus AFGK binaries and PCEBs with M-dwarf companions and find a wide range of possible evolutionary histories for both systems. While TYC 3858-1215-1 will run into dynamically unstable mass transfer that will cause the two stars to merge and evolve into a single white dwarf, TYC 110-755-1 is a progenitor of a cataclysmic variable system with an evolved donor star.